Match Running Performance of Brazilian Professional Soccer Players According to Tournament Types - Aedo-Munoz, E (Montenegrin Sports Academy, 2022)
The present study aimed to report different level games in terms of their external game loads, using data collected from GPS performance indicators in Brazilian soccer teams. We used measures of 464 performances of professional soccer athletes during the National Tournament (NT=265), State Tournament (ST=89), National Cup (NC=44), and the International Tournament (IT=66). The performance analysis included the assessment of Total (meters) and Relative (meters/minutes) distances; running (>14km/h), and sprinting (>18km/h) distance; the number of sprints (>18km/h and >24km/h); accelerations (above three m/s2), deceleration (less than three m/s2) and jumps (>30 cm); Total and Relative load - per minute. There were differences (p<0.05) in terms of relative distance between NT and ST (102.2 ±9.5 vs. 98.1± 10.3) and between ST and NC (98.1± 10.3 vs. 103.4 ±9.6). In sprints >18km/h NT differed from ST (60.4 ±5.9 vs 52.7 ±19.9). In sprints >24km/h differences could be found between NT and ST (10.7 ±5.9 vs 8.7 ±5.4). In Total Load NT differed with respect to ST (908.6 ±141.5 vs. 852.7 ±138.5) In Relative Load differences were reported between NT and ST (10 ±1.2 vs. 9.3 ±1.4) and IT (10 ±1.2 vs. 9.4 ±1.4), and between ST and NC (9.3 ±1.4 vs. 10.0 ±1.4). Finally, concerning deceleration, NT differed when compared to ST (36.1 ±9.9 vs. 32 ±11) as well as ST differed from IT (32 ±11 vs. 37.5 ±9.7). The present results make it possible to create specific training games according to tournament level associated with the predominant activities performed during the competition. © 2022 by the author(s). License MSA, Podgorica, Montenegro. All Rights Reserved.